Comparison of RAFT‐derived poly(vinylpyrrolidone) verses poly(oligoethyleneglycol methacrylate) for the stabilization of glycosylated gold nanoparticles. Issue 7 (26th January 2017) - Sze Ieong, Nga; Biggs, Caroline I.; Walker, Marc; Gibson, Matthew I.
ABSTRACT: Carbohydrates dictate many biological processes including infection by pathogens. Glycosylated polymers and nanomaterials which have increased affinity due to the cluster glycoside effect, are therefore useful tools to probe function, but also as prophylactic therapies or diagnostic tools. Here, the effect of polymer structure on the coating of gold nanoparticles is studied in the context of grafting density, buffer stability, and in a lectin binding assay. RAFT polymerization is used to generate poly(oligoethyleneglycol methacrylates) and poly( N ‐vinylpyrrolidones) with a thiol end‐group for subsequent immobilization onto the gold. It is observed that poly(oligoethylene glycol methacrylates), despite being widely used particle coatings, lead to low grafting densities which in turn resulted in lower stability in biological buffers. A depression of the cloud point upon nanoparticle immobilization is also seen, which might compromise performance. In comparison poly(vinylpyrrolidones) resulted in stable particles with higher grafting densities due to the compact size of each monomer unit. The higher grafting density also enabled an increase in the number of carbohydrates which can be installed per nanoparticle at the chain ends, and gave increased binding in a lectin recognition assay. These results will guide the development of new nanoparticle biosensors with enhanced specificity, affinity, and stability. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 55, 1200–1208 Abstract : A critical comparison is made between a commonly used comb‐shaped polymer (POEGMA) and linear polymer (PVP) for their stabilization of gold nanoparticles for biosensing. It is shown that the PVP gives rise to higher grafting densities and improved saline stability. Furthermore, introduction of carbohydrates at the polymer end‐group resulted in more binding to a model lectin for the PVP system compared with POEGMA. This highlights the crucial role of the polymer corona for plasmonic nanosensors.